2018
DOI: 10.3390/su10041028
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Assessments of Urban Employees’ Pension Plan of China

Abstract: In the uncertain environment of population and economy; the pension plan for urban employees in China is under threat from various types of financial risk. This paper mainly builds a comprehensive risk assessment system to evaluate the solvency sustainability of the urban employees’ pension plan of China. Specifically, we forecast annual accumulative net asset; actuarial balance; and potential support ratio for the next seventy years. To account for the impact of demographic uncertainty on long-term finances, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 20 publications
4
15
0
Order By: Relevance
“…In the long run, neither the fertility policy adjustment nor the retirement delay would fundamentally solve the pension payment crisis. The results of the general trend of an expanding pension gap are consistent with the findings of Zhao et al [20] as well as Tian and Zhao [43].…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…In the long run, neither the fertility policy adjustment nor the retirement delay would fundamentally solve the pension payment crisis. The results of the general trend of an expanding pension gap are consistent with the findings of Zhao et al [20] as well as Tian and Zhao [43].…”
Section: Resultssupporting
confidence: 91%
“…Salditt and Whiteford [19] analyzed pension sustainability issues and pointed out that the limited coverage, low management level, empty individual account, poor returns, high replacement rates, and low retirement age compromise obstacles to the pension system. Using statistical models integrated with the Lee-Carter model, Zhao et al [20] accessed the solvency of the pension plan and concluded that under existing socio-economic policies and pension regulations, the payment burden of the pension system would increase rapidly. Moreover, they observed that delaying retirement age could not fundamentally solve the sustainability crisis of the pension system.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Zheng and Liao (2017) [41] established the basic pension contributions and expenditures forecasting model under the assumption that payment status and retirement age were random variables, and they verified the accuracy of the prediction model with Beijing data. Zhao (2018) [42] assessed the solvency sustainability of UEEPP in China by a stochastic simulation method.…”
Section: Literature Reviewmentioning
confidence: 99%